SCHOOL, PARENTS, AND COMMUNITY COLLABORATION IN DEVELOPING STUDENTS ENVIRONMENTAL AWARENESS - Priatmoko, Sigit; Sholihah, Saidatus (JMIE (Journal of Madrasah Ibtidaiyah Education), 2023)
Currently, environmental damage has become a global issue that urgently needs to be resolved. One of the ways to prevent environmental damage is to develop environmental awareness within students. This strategy requires strong collaboration between schools, parents, and the community. The aims of this study was to find out the collaboration between schools, parents, and the community in developing students' environmental care attitudes. This study employed case study design. The process of collecting data using semi structured interview, non-participant observation, and documentation. Data analysis through several stages, namely data collection, data condensation, data display, and drawing conclusions. The validity of the data was obtained through source and method triangulation and member checks. The results of the study show that schools, parents and the community take on their respective roles according to their main duties and functions. At the planning stage, the school acts as an initiator, parents and the community help provide suggestions. At the implementation stage, the school acts as the primary responsibility, parents as student assistants, and the community as school partners. At the evaluation stage, the school organizes the process and parents help through the behavior checklist sheet. Finally, at the follow-up stage, schools and communities collaborate to improve program quality, while parents accompany students during follow-up activities.